El lenguaje corporal y simbología en la danza folklórica. :análisis de caso; grupo de danza folklórica de la UPS - Yépez Navarrete, Katherine Estefanía (2014)
This thesis will address the body language and symbolism of folk dance as a communication tool, based case study group folk dance from the UPS. The study is based on a concept of communication, from the orchestral model, symbolic interactionism and finally the axioms of communication. Taking communication as processes in which people can interact, knowing it will always be paramount cultural context, understanding that all within the same communicates. Starting from the above, it is important and issues of interaction where a group of individuals come together to make approximations and cultural approaches are discussed. Analysis mainly of daily life amidst dance performances given by developed addressing this as such. Dance is a form of communication, taken from antiquity; in the use of rituals, celebrations and others.